Biocompatible chitin/carbon nanotubes composite hydrogels as neuronal growth substrates. (15th October 2017) - Wu, Shuangquan; Duan, Bo; Lu, Ang; Wang, Yanfeng; Ye, Qifa; Zhang, Lina
Graphical abstract: Highlights: Chitin/carbon nanotubes (Ch/CNT) composite hydrogels were prepared from chitin/NaOH/urea aqueous solution by blending with modified CNTs. The Ch/CNT composite hydrogels exhibited nanofibrillar network structure, excellent mechanical properties and biodegradability in vitro. The Ch/CNT composite hydrogels with good biocompatibility could enhance the proliferation of neuronal cells and Schwann cells in vitro. The incorporation of CNTs could significantly enhance cell adhesion, proliferation and neurite outgrowth of neuronal cells. Abstract: In the past decades, extensive studies have demonstrated that carbon nanotubes (CNTs) could promote cell adhesion, proliferation and differentiation of neuronal cells. However, the potential cytotoxicity in biological systems severely restricted the utilization of CNTs as substrates for neural growth. In this study, biocompatible chitin/carbon nanotubes (Ch/CNT) composite hydrogels were developed via blending modified CNTs with chitin solution in 11 wt% NaOH/4 wt% urea aqueous system, and subsequently regenerating in ethanol. As the CNTs were dispersed homogeneously in chitin matrix and combined with chitin nanofibers to form a compact and neat Ch/CNT nanofibrous network through intermolecular interactions, such as electrostatic interactions, hydrogen bonding and amphiphilic interaction, etc. The tensile strength and elongation at break of the Ch/CNT composite hydrogels were obviously enhanced, and the swelling ratio decreased. In addition, the Ch/CNT hydrogels exhibited good hemocompatibility, biodegradation in vitro and biocompatibility without cytotoxicity and neurotoxicity nature to neuronal and Schwann cells (PC12 cells and RSC96 cells). Especially, the Ch/CNT3 composite hydrogels exhibited significant enhancement of the neuronal cell adhesion, proliferation and neurite outgrowth of neuronal cells with a great increase in both the percentage and the length of neurites. Therefore, we provide a simple and efficient approach to construct the novel Ch/CNT hydrogels as neuronal growth substrates for the potential application in nerve regeneration.